2007
DOI: 10.1007/s10661-007-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and heavy metal concentrations in surface soils and vegetables of Feni district in Bangladesh

Abstract: An investigation of various heavy metals including the arsenic (As) poisoning in soils and vegetables in five upazillas under Feni district of Bangladesh was performed by neutron activation technique using the neutron irradiation facilities of TRIGA MARK II research reactor at Bangladesh Atomic Energy Research Establishment (BAERE), Savar, Dhaka. A total of 30 samples (15 surface soils and 15 foodstuffs) were studied in five Upazillas namely as, Sonagazi, Dagan Bhuiya, Feni Sadar, Fulgazi and Parsuram of Feni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 18 publications
1
13
5
Order By: Relevance
“…Therefore, it is a potential route of entry of As and other toxic elements into crops and vegetables grown in the As contaminated areas. Some reported studies of As concentrations of Bangladeshi vegetables sampled various vegetables from regions of Bangladesh that are known to have high concentration of As in the ground water [2,27,55]. Alam et al [2] reported that the highest concentrations of As were detected in different types of vegetables including ghotkol, taro (loti from Arum plant) and snake gourd at 446, 440 and 489 µg/kg (dry weight) respectively, and a mean of 225 µg/kg (dry weight) for all vegetables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is a potential route of entry of As and other toxic elements into crops and vegetables grown in the As contaminated areas. Some reported studies of As concentrations of Bangladeshi vegetables sampled various vegetables from regions of Bangladesh that are known to have high concentration of As in the ground water [2,27,55]. Alam et al [2] reported that the highest concentrations of As were detected in different types of vegetables including ghotkol, taro (loti from Arum plant) and snake gourd at 446, 440 and 489 µg/kg (dry weight) respectively, and a mean of 225 µg/kg (dry weight) for all vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Their study focused on the Pabna region of Bangladesh and the situation may be different for other regions. More recently, a value of 105 µg/day, just from consumption of vegetables was estimated for Bangladeshis [55] (see Table 4). Although there are differences in the estimates of daily intake between different studies, overall the concentration of As in the Bangladeshi diet is very high and may explain the observation of adverse health outcomes in the Bangladeshi population.…”
Section: Discussionmentioning
confidence: 99%
“…2) are considered to mainly originate from the regional lithogenic factors of natural parent soils as reported by previous reports (Zhou et al 2008;Franco-Uría et al 2009). However, the elements in PC2 might also derive from the anthropogenic factors such as the agrochemical materials (including fertilizers and pesticides) according to the previous reports (Nziguheba and Smolders 2008;Karim et al 2008). In the present study, the mean contents of the three elements in most of the soil samples are not significantly higher than the background values as shown in Table 2, which indicates that these elements in soils may mainly originate from the regional lithogenic sources.…”
Section: Principal Component Analysismentioning
confidence: 96%
“…It is contrary to the concept of green analytical chemistry, and solid sample preparation appears to be more preferable from this point of view. X-ray fluorescence, [8][9][10] neutron activation analysis, 11,12 and laser induced breakdown spectroscopy 6,13,14 are applied for direct analysis of soil in the form of pellets or powders. However, these methods are used not as often as ICP-AES due to the considerable matrix effects and require the calibration samples similar to the analyzed ones.…”
Section: Introductionmentioning
confidence: 99%